Abstract 252: The outcomes and complications in patients undergoing subclavian‐carotid artery bypass surgery: A case series - Serena Wong (Stroke: Vascular and Interventional Neurology)
Introduction Endovascular intervention has become the mainstay of treatment for acute ischemic stroke. However, in certain cases, open surgery is the only option to achieve revascularization. This study presented two patients with symptomatic common carotid artery occlusion (CCAO) who subsequently underwent subclavian‐carotid artery bypass surgery using the polytetrafluorethylene graft. The complications of the procedure and patient’s outcomes were discussed. Methods We identified two patients who were admitted to our medical center between January 2022 to December 2022 for subclavian‐carotid artery bypass procedure. Clinical data were reviewed retrospectively. Results Case 1. A 69‐year‐old woman with a history of lung cancer, hypertension, chronic tobacco use, atherosclerosis, and known calcified plaque at the left carotid bifurcation on dual antiplatelet therapy presented with acute onset of expressive aphasia and right hemiparesis due to acute left CCAO. Endovascular procedure was deferred due to difficult arterial access. An endarterectomy of CCA, eversion endarterectomy of external carotid artery, and subclavian‐carotid artery bypass surgery were performed. She developed neck hematoma post‐operatively, requiring evacuation. She was discharged to acute rehabilitation facility and eventually home. Six months after surgery, she still had severe expressive aphasia and spasticity of the right arm and leg (Figure A‐C). Case 2. A 79‐year‐old man with a strong family history of arterial dissection, hypertension, coronary artery disease, and obesity experienced intense chest pain and left hemiparesis secondary to Type A aortic dissection with extension from the innominate artery to the right carotid bifurcation. Endovascular intervention was deferred given the angulation of aortic arch after surgical repair. Decision was made to perform subclavian‐carotid artery bypass surgery. Post‐operatively, he had evacuation of neck hematoma. He also had tracheostomy and gastrostomy tube placement prior to discharge to skilled nursing facility. At 6‐month follow up, he could ambulate with a walker and oral diet was resumed (Figure D‐F). Conclusion CCAO is a rare condition, and there is no prospective randomized trial that compares various treatment strategies for symptomatic CCAO. Consistent with the findings of our study, bypass surgeries have been shown as an effective treatment to prevent further ischemic infarct in patients with symptomatic CCAO. Both patients in our study survived at 6‐month follow up with no recurrence of stroke. Additionally, no other surgical complications were noted except for neck hematoma. Bypass surgery was performed as a salvage procedure for both patients after they suffered from stroke. Early identification of CCAO and collaboration between vascular surgeon and endovascular interventionist would maximize the benefit of this life‐saving procedure to the appropriate candidates.